2019
DOI: 10.1038/s41586-019-1819-6
|View full text |Cite
|
Sign up to set email alerts
|

RGF1 controls root meristem size through ROS signalling

Abstract: Stem cell niche and root meristem size are maintained by intercellular interactions and signaling networks of a peptide hormone, Root Meristem Growth Factor 1 (RGF1). How RGF1 regulates root meristem development is an essential question to understand stem cell function. Although five receptors of RGF1 have been identified, the downstream signaling mechanism remains unknown. Here, we report a series of signaling events following RGF1 action. The RGF1-receptor pathway controls the distribution of reactive oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(140 citation statements)
references
References 23 publications
5
135
0
Order By: Relevance
“…RGF1 treatment resulted in enhanced O 2accumulation in the meristematic zone, thus enhancing the stability of PLT2 protein to increase the proximal root meristem size. Consistent with this, the ritf1 mutants displayed reduced proximal root meristem size and RGF1-induced O 2accumulation, suggesting that RITF1 has a crucial role in mediating RGF1 signaling (Yamada et al 2020) (Fig. 3B).…”
Section: Rlk-mediated Signaling Regulates the Maintenance Of The Proxsupporting
confidence: 73%
“…RGF1 treatment resulted in enhanced O 2accumulation in the meristematic zone, thus enhancing the stability of PLT2 protein to increase the proximal root meristem size. Consistent with this, the ritf1 mutants displayed reduced proximal root meristem size and RGF1-induced O 2accumulation, suggesting that RITF1 has a crucial role in mediating RGF1 signaling (Yamada et al 2020) (Fig. 3B).…”
Section: Rlk-mediated Signaling Regulates the Maintenance Of The Proxsupporting
confidence: 73%
“…Furthermore, a recent discovery has uncovered the regulation mechanisms of root meristem development under the RGF1-receptor pathway. The RGF1-RGFR signaling pathway modulates ROS distribution along the developmental zones of the Arabidopsis root and enhances the PLT2 protein stability [ 45 ]. Genetic evidence also showed that the RGF1-receptor pathway is required to maintain proper gradients of PLT proteins in the proximal meristem [ 41 ].…”
Section: The Roles Of Tyrosine-sulfated Peptides and Their Receptomentioning
confidence: 99%
“…Despite the ligand-receptor pairs having been identified, the downstream signaling of RGF1 remained elusive and the molecular mechanisms involved in root meristem development and the PLT1/2 stability were still unknown. Since RGF1 is received in the meristematic zone by the receptors, the meristematic zone-specific transcriptome analysis after RGF1 treatment was conducted to understand the downstream gene in the meristematic zone [ 45 ]. The transcriptome analysis detects significant alteration of expression of the genes related to ROS suggesting that RGF1 might signal through a ROS intermediate to control the size of the meristematic zone.…”
Section: The Roles Of Tyrosine-sulfated Peptides and Their Receptomentioning
confidence: 99%
See 2 more Smart Citations